True grit (1969) [videorecording (DVD)] - Hathaway, Henry, 1898-1985; Wayne, John, 1907-1979; Campbell, Glen, 1936-2017; Darby, Kim, 1947-; Portis, Charles (The John Wayne collection, 2007)
U.S. Marshal Rooster Cogburn helps a headstrong young girl find the man who murdered her father in Native American territory and fled with the family savings. When Rooster's employer insists on accompanying the old gunfighter, sparks fly. The situation goes from troubled to disastrous when an inexperienced Texas Ranger joins the party.